2008
DOI: 10.1007/s00104-008-1488-8
|View full text |Cite
|
Sign up to set email alerts
|

Ergebnisse der Sigmaresektion bei akuter und komplizierter Divertikulitis

Abstract: Laparoscopic sigmoid resection can be performed in cases of complicated diverticulitis without significantly increasing their overall morbidity. Because of the lower complication rate, we recommend that patients with acute sigmoid diverticulitis receive initial antibiotic treatment and then undergo late elective laparoscopic sigmoid resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
3
4
1
Order By: Relevance
“…Surgical complications are among the major outcome parameters that might influence the choice between the two treatment strategies. In contrast to previous published data [2, 17, 22], surgical complications in the present study were slightly lower in group A than in group B. Intra‐abdominal abscess, SSI, and anastomotic leak appeared to be the most important surgical complications in this study, which might be explained by the presence of residual inflammatory tissue, especially in group A patients. The slightly lower percentage of severe surgical complications in group A (risk 9% versus 10%) could be interpreted as an advantage compared to group B.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Surgical complications are among the major outcome parameters that might influence the choice between the two treatment strategies. In contrast to previous published data [2, 17, 22], surgical complications in the present study were slightly lower in group A than in group B. Intra‐abdominal abscess, SSI, and anastomotic leak appeared to be the most important surgical complications in this study, which might be explained by the presence of residual inflammatory tissue, especially in group A patients. The slightly lower percentage of severe surgical complications in group A (risk 9% versus 10%) could be interpreted as an advantage compared to group B.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to patients’ needs such as increased comfort and avoiding unnecessary days of hospitalization, early elective surgery has become increasingly popular. Both group A and group B had a postoperative hospital stay of 8 days, which is comparable to other studies [1, 2, 17, 22]. As presented in our multivariate analysis, neither timing of operation nor severity of diverticulitis had a significant impact on length of hospital stay.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The operation time has proved to be a suitable parameter for characterizing the learning curve [ 24 , 25 ]. The operative times, calculated on the basis of the dissection and suturing time, recorded in this study are comparable with the data already published [ 17 , 23 , 29 , 30 ]. The operation time in the present study was significantly reduced through the combination of ultrasonic scissors and bipolar coagulation mode (BDD).…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, other series have indicated that early surgery was associated with a significant increase in conversion rate (37.7% vs 12.9%, P < 0.001) and longer hospitalization (13.5 vs 10.5 days; P < 0.001) 34. A prospective German study evaluating the optimal timing of laparoscopic sigmoid resection for uncomplicated and complicated diverticular disease showed that patients having early surgery (4–8 days after initiation of antibiotic therapy, n = 244) incurred in an increased number of conversions (9.7% vs 0.9%), increased minor morbidity (25.9% vs 12.9%) and wound infection rates (16.4% vs 4.6%) than patients who had delayed surgery 35. Based on this data we continue favoring delaying elective surgery by an interval of 4–6 weeks after the latest disease episode.…”
Section: Elective Surgical Management Of Uncomplicated Diverticular Dmentioning
confidence: 99%